New Era-New Challenge - Linstone, Harold A. (Technological forecasting and social change)
On the occasion of the 25-year anniversary of the Journal, the editor discusses the challenge of the coming decades : to deal with the combined impact of the population and technology explosions, which are creating the shrunken global megalopolis. This complex system, in which everything interacts with everything, cries out for new thinking, with new modes of inquiry and new metaphors. The multiple perspective concept is used as an illustration, with particular focus on the discounting dilemma and the impact of information technology on organization.